FTIR analysis of an artwork by Lars Pirak (MOM/2020/69) (project number RAÄ-2021-1062) (incl. instrument report) - hacke, marei (Swedish National Heritage Board, 2024)
FTIR data (incl. Instrument report) of samples from Lars Pirak's artwork Without namn (MOM/2020/69) at Moderna Museet, Stockholm, Sweden.

Samples are:

01: paint02: canvas fibres03: glue (used to adhere canvas to fibre board)04: filler (used to fill space between adjoining sections of fibre board)

Object: Without name (https://sis.modernamuseet.se/sv/objects/104484/utan-titel?ctx=10cdad7191a8523c66230db355a8c0c9a85dc18a&idx=4)

Artist: Lars Pirak

Owner: Moderna museet, Stockholm, Sweden (https://www.modernamuseet.se/stockholm/sv/)

Data collected at the Swedish National Heritage Board (www.raa.se), project number Dnr RAÄ-2021-1062.
Keywords: Heritage Science; RAÄ-2021-1062; Lars Pirak; FTIR spectroscopy; Moderna Museet; MOM/2020/69; History and Archaeology; Historia och arkeologi